2012
DOI: 10.1124/jpet.112.199513
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Guanidine Analogs as Sigma Receptor Ligands for Potential Anti-Stroke Therapeutics

Abstract: Currently, the only Food and Drug Administration-approved treatment of acute stroke is recombinant tissue plasminogen activator, which must be administered within 6 hours after stroke onset. The pan-selective s-receptor agonist N,N9-di-o-tolylguanidine (o-DTG) has been shown to reduce infarct volume in rats after middle cerebral artery occlusion, even when administered 24 hours after stroke. DTG derivatives were synthesized to develop novel compounds with greater potency than o-DTG. Fluorometric Ca 21 imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Since SGCs in the DRG play a similar role as astrocytes in CNS [ 46 ] and come from the same embryological origin as Schwann cells [ 69 ], our finding of σ1R in SGCs is consistent with these previous reports. After ischemic brain injury, σ1Rs are upregulated in reactive astrocytes as well as neurons [ 67 ], which reduces glutamate accumulation and inhibits interleukin-1β expression and microglial migration to abate ischemia-induced inflammatory reaction [ 70 , 71 ] (reviewed in [ 7 ]). Our data show that peripheral nerve injury differs from ischemic brain injury since σ1R decreases in the ganglia in which axotomized neurons reside.…”
Section: Discussionmentioning
confidence: 99%
“…Since SGCs in the DRG play a similar role as astrocytes in CNS [ 46 ] and come from the same embryological origin as Schwann cells [ 69 ], our finding of σ1R in SGCs is consistent with these previous reports. After ischemic brain injury, σ1Rs are upregulated in reactive astrocytes as well as neurons [ 67 ], which reduces glutamate accumulation and inhibits interleukin-1β expression and microglial migration to abate ischemia-induced inflammatory reaction [ 70 , 71 ] (reviewed in [ 7 ]). Our data show that peripheral nerve injury differs from ischemic brain injury since σ1R decreases in the ganglia in which axotomized neurons reside.…”
Section: Discussionmentioning
confidence: 99%
“…Previously studies have shown that σ receptor activation can mitigate intracellular calcium dyshomeostasis in neurons and microglia following ischemia, acidosis, ATP and amyloid-β exposure (Katnik et al, 2006; Herrera et al, 2008; Hall et al, 2009a; Cuevas et al, 2011a,b; Behensky et al, 2013a,b,c; Mari et al, 2015). Sustained elevations in intracellular calcium are associated with the initiation of apoptosis (Mattson and Chan, 2003), and thus by preserving intracellular calcium homeostasis, afobazole may prevent cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In all experiments involving ischemia, the chemical ischemia model used previously in our laboratory was employed (Katnik et al, 2006; Mari et al, 2010; Cuevas et al, 2011a,b; Behensky et al, 2013a). Briefly, culture media was supplemented with 4 mM sodium azide to inhibit mitochondrial function and cells were incubated in this media for the indicated times.…”
Section: Methodsmentioning
confidence: 99%
“…Microglia, and potentially astroglia, express sigma1-receptors, and therefore can be directly affected by exposure to methamphetamine and cocaine. Despite some reports that selective sigma1-receptor activation has been shown to inhibit microglial motility, cytokine release, and intracellular Ca 2+ in response to lipopolysaccharide (LPS), monocyte chemoattractant protein-1, and ATP (Hall, Herrera, Ajmo, Jr., Cuevas, & Pennypacker, 2009), while ligands with agonist properties more often found to activate proinflammatory microglial responses (Gekker et al, 2006; Yao et al, 2011; Cuevas, Rodriguez, Behensky, & Katnik, 2011; Behensky et al, 2013). The evidence for astroglial expression of sigma1-receptors is less well established and is based on their expression in a human fetal astroglial SVG cell line (Ben-Ami, Kinor, Perelman, & Yadid, 2006), or on ligand binding profiles, or effects in primary astrocytes (Mattson, Rychlik, & Cheng, 1992; Prezzavento et al, 2007) and glioblastoma cell lines (Thomas et al, 1990).…”
Section: Molecular Biology and Physiology Of The Gliamentioning
confidence: 99%